Performance coordination design method applied to replaceable artificial controllable plastic hinge for precast concrete beam-column joints. (15th April 2022) - Yuan, Yujie; Huang, Hua; Ye, Yanxia; Li, Ming; Sun, Hongye
Abstract: This report proposes a novel performance coordination design method wherein the precast beam-column joint cooperates with an artificial controllable plastic hinge (ACPH). This approach introduces three deformation coordination coefficients to manage the bearing capacity, rotational stiffness, and deformability between the ACPH and the reinforced concrete components. Ultimately, structural deformation resulting from seismic action is mainly concentrated on the ACPH to prevent damage to the concrete components. The design process and philosophy were translated into formulas and compiled in this paper. The ACPH performance and design process efficacy were explored using a hysteresis test performed on a ½-scale specimen and simulated using the finite element models. The results indicated that the precast reinforced concrete structure containing an ACPH exhibited excellent deformability and ductility, while guaranteeing structural integrity. Highlights: A novel performance coordination design method applied to artificial controllable plastic hinge (ACPH) was proposed. This paper introduced 3 deformation coordination coefficients to manage performances between ACPH and concrete component. Design formula cooperating with design process and philosophy were put forward in this paper.